2014
DOI: 10.1254/jphs.14017fp
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Induces Apoptosis Through Mitochondrial Intrinsic Pathway and Suppression of ERK1/2 MAPK in HeLa Cells

Abstract: Abstract. Ursolic acid (UA), a natural pentacyclic triterpenoid compound, has been demonstrated to induce apoptosis in various tumors. The aim of the present study was to elucidate the molecular mechanisms of UA-induced apoptosis in HeLa cells. Here, we reported that UA induced apoptosis through the mitochondrial intrinsic pathway in HeLa cells, as shown by release of cytosol cytochrome c, activation of caspase-9 and -3, reduction of Bcl-2 and Bcl-xL, and increase of Bax and Bak. UA down-regulated the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…27,28 Bcl-2 and Bax are essential for apoptosis and in the eventual activation of caspase in Bcl-2 family. 31 In this study, we showed that administration of TQ markedly decreased the Bax/Bcl-2 ratio induced by D-GalN/LPS (Fig. 30 Regardless of how the JNK signaling regulates the Bcl-2 superfamily members, as a whole, Bax/Bcl-2 ratio determine whether the cell survives or apoptosis.…”
Section: Discussionmentioning
confidence: 64%
“…27,28 Bcl-2 and Bax are essential for apoptosis and in the eventual activation of caspase in Bcl-2 family. 31 In this study, we showed that administration of TQ markedly decreased the Bax/Bcl-2 ratio induced by D-GalN/LPS (Fig. 30 Regardless of how the JNK signaling regulates the Bcl-2 superfamily members, as a whole, Bax/Bcl-2 ratio determine whether the cell survives or apoptosis.…”
Section: Discussionmentioning
confidence: 64%
“…In this regard, UA seems to be an interesting target to develop new formulations to be used in human health, because different reports demonstrated its multivalent activities against pathological conditions. UA was demonstrated to be active against different tumor cell lines (Chuang et al., 2016, Aguiriano-Moser et al., 2015, Kim and Moon, 2015), its anti-tumoral effect being associated to apoptosis induction by intrinsic and extrinsic pathways of death (Li et al., 2014, Meng et al., 2015, Zhang et al., 2016, Villar et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluating the pharmacological mechanism of UA action have focused on its anticancer, hepatoprotective, antihyperlipidemic, and anti-depression effects. These studies have revealed that UA modulates signal transducer and activator of transcription 3 (STAT3) [7], mitogen-activated protein kinases (MAPKs) [8], peroxisome proliferator-activated receptors (PPARs) [9], transforming growth factor-b (TGF-b)/Smad signaling [10], and nuclear factor-kB (NF-kB) [11]. However, the effects of UA on bone metabolism remain unclear.…”
Section: Introductionmentioning
confidence: 99%